2002
DOI: 10.1038/sj.npp.1300132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Monoxide on Dopamine and Glutamate Uptake and cGMP Levels in Rat Brain

Abstract: After the recognition of nitric oxide (NO) as a messenger molecule in the nervous system, carbon monoxide (CO) has received attention with similar properties. The present study aims to elucidate the effects of CO on synaptosomal dopamine ( 3 H-DA) and glutamate ( 3 H-Glu) uptake and on cGMP levels; possible interaction between NO and CO systems was also evaluated. Our results provide evidence for the inhibition of DA and Glu uptake by CO in a time-, dose-, and temperature-dependent manner in rat striatum and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Several previous studies have indicated that CO and RyR-dependent DA release also occurs in mammals. A microdialysis study has shown that CO increases the extracellular DA concentration in the rat striatum and hippocampus (Hiramatsu et al, 1994), either through increased DA release or inhibition of DA reuptake (Taskiran et al, 2003). Also, pharmacological stimulation of RyRs has been reported to induce DA release in the mice striatum (Oyamada et al, 1998;Wan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have indicated that CO and RyR-dependent DA release also occurs in mammals. A microdialysis study has shown that CO increases the extracellular DA concentration in the rat striatum and hippocampus (Hiramatsu et al, 1994), either through increased DA release or inhibition of DA reuptake (Taskiran et al, 2003). Also, pharmacological stimulation of RyRs has been reported to induce DA release in the mice striatum (Oyamada et al, 1998;Wan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…36 We have observed earlier that CO treatment results time, dose and temperature dependent inhibition of dopamine and glutamate uptake in synaptosomes which was regionally selective and sexually dimorphic. 3 Although there is limited information about sex-related differences in CO mediated toxicity, a recent case report suggests differential vulnerability of the male and female brain to CO poisoning. 37 In conclusion, the data presented in this study supports the destructive role of CO in mitochondria via inhibiting cytochrome c oxidase and generating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a role for carbon monoxide (CO) as a neurotransmitter or neuromodulator in the nervous system. [1][2][3] Although a very small amount of CO is generated endogenously by the action of heme oxygenase (HO) during heme catabolism, larger amounts of CO from exogenous sources can cause lethal poisoning. 4,5 Pathophysiology of CO poisoning is mostly attributed to its high affinity for binding hemoglobin to form carboxyhemoglobin (COHb) thereby reducing the oxygen-carrying capacity of the blood.…”
Section: Introductionmentioning
confidence: 99%
“…As in neurons, Ca 2+ influx results in astrocytic Ca 2+ signaling. AMPA-evoked Ca 2+ influx into astrocytes has been associated with a weak expression of GluA2 324325326327328329330. CO has a pivotal role in calcium signaling in both neurons and astrocytes.…”
Section: Possible Biochemical Effects Of Carbon Monoxide On Astrocytementioning
confidence: 99%